2004
DOI: 10.1590/s1677-04202004000300003
|View full text |Cite
|
Sign up to set email alerts
|

Growth, photosynthesis, nodule nitrogen and carbon fixation in the chickpea cultivars under salt stress

Abstract: Four cultivars of chickpea, two of them of Mediterranean origin (kabuli), CSG 9651, BG 267 and two Indian (desi) types, CSG 8962, DCP 92-3, differing in their salt sensitivities were identified after screening ten genotypes in saline soils. The cultivars CSG 9651 and CSG 8962 were salt tolerant while BG 267 and DCP 92-3 were salt sensitive, respectively. The seeds of different cultivars were inoculated with Mesorhizobium ciceri, strain F: 75 and the plants were grown in the greenhouse. After the establishment … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
34
0
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 58 publications
(43 citation statements)
references
References 24 publications
7
34
0
2
Order By: Relevance
“…The data presented in Table 1 are consistent by the results obtained by Garg and Singla (2004) or Netondo et al(2004) with chickpea or sorghum plants. These authors report that stomatal closure is a prime constraint to photosynthesis by limiting CO 2 flux into the leaves of salt-stressed plants.…”
Section: Discussionsupporting
confidence: 91%
See 4 more Smart Citations
“…The data presented in Table 1 are consistent by the results obtained by Garg and Singla (2004) or Netondo et al(2004) with chickpea or sorghum plants. These authors report that stomatal closure is a prime constraint to photosynthesis by limiting CO 2 flux into the leaves of salt-stressed plants.…”
Section: Discussionsupporting
confidence: 91%
“…The decrease in Chl may be attributed to increased chlorophyllase activity (Sudhakar et al, 1997). Several investigators have shown that Rubisco activity in leaves is inhibited by salinity, similar to the degradation of leaf Chl (Garg and Singla, 2004). The decrease in Rubisco activity caused by salt exposure may be attributed to the sensitivity of this enzyme to chloride ions (Seeman and Chritchley, 1985).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations